Karamzin’s dialogue with Sterne’s literary tradition in the novel The Letters of a Russian Traveller (devices of «Sterne’s plot» artistic design) - Алпатова, Татьяна (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2012)
The article is devoted to the study of Sterne’s reminiscences in the novel The Letters of a Russian Traveller by Karamzin. They are studied as a globally organized artistic system, linked with the concept of English literature, shaped in Karamzin’s works between 1780 –1790, as well as with the writer’s thoughts on other philosophical and aesthetic problems. «Sterne’s plot» in the novel The Letters of a Russian Traveller by Karamzin develops together with other plots, whose cooperation formed a forward-looking dynamic poetic manner of narration in the book.